Insights Into the Impacts of BRCA Mutations on Clinicopathology and Management of Early-Onset Triple-Negative Breast Cancer - Ye, Fugui; He, Min; Huang, Liang; Lang, Guantian; Hu, Xin; Shao, Zhimin; Di, Genhong; Cao, Ayong (Frontiers in Oncology, 2021)
Background. Little is known regarding the clinicopathologic characteristics, oncologic outcomes, and treatment strategies that could be ascribed to BRCA mutation in early-onset triple-negative breast cancer (eTNBC). Methods. eTNBC patients who underwent BRCA genetic testing were derived from our clinical database between 2012 and 2018. Differences in clinical features and pathologic characteristics were examined in groups divided by BRCA mutation status, and the contribution of germline mutations in conjunction with treatment modalities to survival outcomes was determined. Results. Of the 355 qualifying eTNBC patients, 67 (18.87%) were BRCA mutated and 288 (81.13%) were BRCA wild. Overall, median age at diagnosis was 34 years (range, 24-40 years) in the BRCA mutated subgroup and 35 years (range, 21-40 years) in BRCA wild. The majority of clinicopathologic parameters were parallel; however, tumor size (P =0.07) and nuclear grade (P =0.08) tend to be more aggressive in the BRCA mutated subgroup. Compared with BRCA wild patients, BRCA mutated patients had a higher likelihood of receiving anthracyclines and taxanes-based combination chemotherapy (P =0.04) and tend to be lower tumor burden (P =0.01). After approximately 5-year median follow-up, the overall survival (OS) (P =0.021) and breast cancer-specific survival (BCSS) (P =0.004) in BRCA mutated patients were superior to those in their BRCA wild counterparts. Intriguingly, the clinical outcomes were comparable in patients with breast conserving surgery (BCS) regardless of BRCA mutations and in patients with BRCA mutations in spite of surgical schedules. Conclusions. These results suggest that eTNBC patients with BRCA mutations are prone to better OS and BCSS, which might be largely attributed to more benefit from anthracyclines and taxanes-based chemotherapy. The BCS procedure could be a safe alternative surgical option for eTNBC patients with BRCA mutations. Future studies with substantial numbers of participants are urgently needed to validate whether BRCA mutation eTNBC patients are more sensitive to chemotherapy.